Prevalence of childhood depression in school going adolescents in an urban Indian school - Raja, Dhiraj (Ind Psychiatry J, 2020)
BACKGROUND: Understanding the prevalence of a psychiatric disorder among children is essential for formulating sound public health policy. AIM: This study is aimed to estimate the prevalence of depression in urban school-going adolescents and its association with age, sex, and birth order. MATERIALS AND METHODS: A total of 500 participants in the age group 12–16 years from a working-class community, studying in an urban school, were selected for the study. The children with a score greater than or equal to 19 on the CDI scale were taken for the second phase, and diagnosis of depression was confirmed by a psychiatric consultant through a clinical interview. In clinically diagnosed cases, all help was rendered, including follow-up. RESULTS: The prevalence of clinical depression among school-going children of age group 12–16 years was 8.4%. There was no significant gender difference in the prevalence of clinical depression. Significantly, more children had clinical depression in the age group of 14–16 years than in the 12–14 years of age group. Depressive symptoms were more among children with first birth order. CONCLUSIONS: These results show that depression is common in school going urban adolescents in India and highlight the need for screening school-age children for depression so that early intervention can be provided.